A Desmoid Tumor Involving the Subscapularis Muscle: A Case Report. Issue 1 (January 2019) - Ballatori, Sarah E.; Hecht, Jonathan L.; Lozano-Calderón, Santiago A.
Abstract : Case: A 31-year-old woman developed worsening pain and paresthesia in the neck, shoulder, and arm over a period of 6 years. Magnetic resonance imaging revealed a soft-tissue mass in the subscapular region, with likely involvement of the scapula and the subscapularis muscle. The mass was resected, and the final histologic diagnosis was desmoid-type fibromatosis. Conclusion: Desmoid tumors with subscapularis muscle involvement are exceedingly rare. Although limited range of motion is the more common presentation for these tumors, this case demonstrates that desmoid tumors may present with primarily neurologic symptoms.